2017
DOI: 10.1016/j.carbpol.2016.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replacement of corn starch by whey protein isolate in biodegradable film blends obtained by extrusion

Abstract: The aim of this study was to evaluate the effect of replacing corn starch by whey protein isolated (WPI) in biodegradable polymer blends developed by extrusion. X-ray diffraction showed the presence of a Vh-type crystalline arrangement. The films were homogeneous, indicating strong interfacial adhesion between the protein and the thermoplastic starch matrix (TPS) as observed in scanning electron microscopy. The addition of WPI on TPS matrix promoted an increase in the thermal stability of the materials. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 80 publications
(87 reference statements)
7
38
1
7
Order By: Relevance
“…Starch is a biopolymer present in many plants, such as corn, potato, wheat, rice, and others. The chemical and physical properties of this material have been extensively studied due to its ability to be transformed into thermoplastic starch (TPS) materials through processes of extrusion, injection molding, and thermos‐pressing to produce dense or porous materials . However, TPS has reduced mechanical properties and high sensitivity to moisture.…”
Section: Introductionmentioning
confidence: 99%
“…Starch is a biopolymer present in many plants, such as corn, potato, wheat, rice, and others. The chemical and physical properties of this material have been extensively studied due to its ability to be transformed into thermoplastic starch (TPS) materials through processes of extrusion, injection molding, and thermos‐pressing to produce dense or porous materials . However, TPS has reduced mechanical properties and high sensitivity to moisture.…”
Section: Introductionmentioning
confidence: 99%
“…c. All SPI‐based film exhibited two basal reflection diffraction peaks at 2θ = 8.7 and 19.8°, respectively, which were attributed to the α‐helix and β‐sheet structures of the SPI secondary conformation . After incorporating PDCNTs, the characteristic peak (α‐helix) of the SPI/G/PDCNTs film slightly shifted to a higher angle and became weaker, which suggested that the original crystalline structure of the SPI nanocomposite film had partially collapsed during the interaction between the SPI chains and PDA‐coated CNTs .…”
Section: Resultsmentioning
confidence: 99%
“…After that, there were two main stages of the thermal decomposition of the SPI‐based films. The first stage from 120 to 280°C was mainly attributed to the glycerol degradation . The second stage was from 280 to 450°C, which could be associated with the decomposition of protein backbone .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simple use of packaging reduces the oxygen concentration with the product, aiding in the reduction of oxidation of pigments. 26 Chroma is a measure of colour saturation, 46,47 and it describes the vividness or dullness of a colour, ie, how close the colour is to either grey or the pure hue. 48 A decrease in chroma value was observed for the salmon samples during storage time, indicating a lower colour intensity, ie, an opaque colour.…”
Section: Analyses Of the Salmon Packaged In The Filmsmentioning
confidence: 99%